Religion and Politics; Reconfiguring the Ontology of Political Beings in Taha Abdurrahman’s Thought - Rizky HK, Muhammad (Universitas Muhammadiyah Surakarta, 2025)
This article explores Taha Abdurrahman's reconstruction of the political subject's ontology as a critical response to the secular foundations of modern political thought. In contemporary discourse, the political human is often conceptualized as a rational and autonomous agent (homo civicus), detached from any transcendent or moral obligation. Taha challenges this model by reintroducing two foundational Islamic concepts: al-amanah (divine trust) and al-mīṯāq (primordial covenant). He redefines the political subject as homo moralis, a moral-spiritual being tasked with ethical responsibility toward God and society. Through his iʾtimāniyyah paradigm, Taha offers a political ontology grounded not in power competition, but in moral accountability, ethical testimony, and self-purification (tazkiyah). This article situates Taha's ideas within broader currents in contemporary Islamic philosophy, comparing them to Seyyed Hossein Nasr's perennialism, Mohammed Arkoun's deconstruction, and Abdolkarim Soroush's epistemic pluralism. It argues that Taha's integration of moral theology, linguistic ethics, and spiritual epistemology presents a robust alternative to secular political rationality. Ultimately, Taha's thought lays the groundwork for a renewed Islamic political ontology where governance and citizenship are oriented toward transcendence, moral excellence, and divine remembrance.